The effect of microcrystalline cellulose (MCC) on coating paint film's surface performance as non-stick coating - Sulaiman, Lidya; Abidin, Zul Hazrin Zainal; Zakir, Nur Izzuany Md; Halim, Norhana Abdul; Rusdi, Rusaini Athirah Ahmad; Tajuddin, Hairul Anuar; Azwani Sofia Ahmad Khiar (Emerald Group Publishing Ltd, 2024)
Indexed by WOS